Diagnosis of HPV-associated oropharyngeal squamous cell carcinoma in a middle-income country: report of two new cases - Nascimento de Aquino, Sibele; Farias Bezerra, Hélen Kaline; Rodrigues Louredo, Brendo Vinícius; Ajudarte Lopes, Márcio; Santos-Silva, Alan Roger; Agustin Vargas, Pablo (Journal of Oral Diagnosis, 2024)
Human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma (OPSCC) is a distinct subset characterized by better treatment responses and higher survival rates. Clinical and morphological aspects are crucial for diagnosis. Here we report two additional cases of HPV-associated OPSCC. Case 1: A 46-year-old male smoker and alcoholic presented with a 6 cm asymptomatic destructive ulcer involving multiple areas of the oropharynx. Microscopic analysis revealed non-keratinizing squamous cell carcinoma (SCC) with strong and diffuse cytoplasmatic and nuclear positivity for p16 in the tumor cells on IHC and ISH for HPV16/18 revealed the presence of viral DNA in a dot-like pattern. Case 2: A 53-year-old male smoker and alcoholic complained of dysphagia and exhibited erythematous areas in the uvula. Microscopically, a basaloid SCC was observed. Assessment of p16 expression showed diffuse moderate nuclear and cytoplasmatic positivity and ISH for DNA HPV16/18 also demonstrated dot-like signals. The present cases highlight the clinical and microscopical aspects of HPV-associated OPSCC. Pathologists and clinicians must remain vigilant in identifying HPV-associated OPSCC, even in cases where there is a history of alcohol and tobacco consumption. Assessment of p16 immunohistochemical patterns and ISH analysis are crucial to better understand the scenario of HPV-associated OPSCC in middle-income countries.